BBSome-deficient cells activate intraciliary CDC42 to trigger actin-dependent ciliary ectocytosis - Prasai, Avishek; Ivashchenko, Olha; Maskova, Kristyna; Bykova, Sofiia; Schmidt Cernohorska, Marketa; Stepanek, Ondrej; Huranova, Martina (EMBO reports, 2025)
Bardet-Biedl syndrome (BBS) is a pleiotropic ciliopathy caused by dysfunction of the BBSome, a cargo adaptor essential for export of transmembrane receptors from cilia. Although actin-dependent ectocytosis has been proposed to compensate defective cargo retrieval, its molecular basis remains unclear, especially in relation to BBS pathology. In this study, we investigated how actin polymerization and ectocytosis are regulated within the cilium. Our findings reveal that ciliary CDC42, a RHO-family GTPase triggers in situ actin polymerization, ciliary ectocytosis, and cilia shortening in BBSome-deficient cells. Activation of the Sonic Hedgehog pathway further enhances CDC42 activity specifically in BBSome-deficient cilia. Inhibition of CDC42 in BBSome-deficient cells decreases the frequency and duration of ciliary actin polymerization events, causing buildup of G protein coupled receptor 161 (GPR161) in bulges along the axoneme during Sonic Hedgehog signaling. Overall, our study identifies CDC42 as a key trigger of ciliary ectocytosis. Hyperactive ciliary CDC42 and ectocytosis and the resulting loss of ciliary material might contribute to BBS disease severity.
Keywords: signální transdukce; Cilia; Actin; Actins; Hedgehog Proteins; Cilium; Bardet-Biedl Syndrome; Receptors, G-Protein-Coupled; proteiny hedgehog; CDC42; Signal Transduction; aktiny; Mice; Bardetův-Biedlův syndrom; Ectocytosis; cilie; receptory spřažené s G-proteiny; cdc42 protein vázající GTP; zvířata; Humans; cdc42 GTP-Binding Protein; myši; lidé; Animals